2020
DOI: 10.1186/s12284-020-00376-6
|View full text |Cite
|
Sign up to set email alerts
|

OsVPE3 Mediates GA-induced Programmed Cell Death in Rice Aleurone Layers via Interacting with Actin Microfilaments

Abstract: Background: Vacuolar processing enzymes (VPEs) have been identified as the enzymes that regulate vacuole-mediated programmed cell death (PCD) in plants. The mechanism that VPE regulates the PCD in rice aleurone layers remains unknown. Results: The aleurone layers treated with distilled water exerted caspase-1 and VPE activity, both of which were inhibited by the caspase-1 specific inhibitor Ac-YVAD-CMK but not by the caspase-3 specific inhibitor Ac-DEVD-CHO. However, the caspase-1 and caspase-3 inhibitors weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The dead cells that had experienced PCD could promote the release of auxin (IAA) [ 8 ]. Gibberellin (GA) could also regulate the PCD process of the aleurone layer cells in the grain [ 9 ]. Increasing the level of ABA in maize grains had also been shown to accelerate the process of dehydration in the grains [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dead cells that had experienced PCD could promote the release of auxin (IAA) [ 8 ]. Gibberellin (GA) could also regulate the PCD process of the aleurone layer cells in the grain [ 9 ]. Increasing the level of ABA in maize grains had also been shown to accelerate the process of dehydration in the grains [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the inhibition of rice VPE blocked the depolymerization of actin filaments, which ultimately delayed the fusion of vacuoles, indicating the relation of vegetative type VPEs in mediating the actin filaments related PCD in aleurone layers. (Uemura et al, 2002;Zheng et al, 2017;Zhang et al, 2020). Moreover, abscisic acid (ABA) accumulates in the integument layers to delay aleurone vacuolation and induce seed dormancy (Bethke et al, 1999;Bethke et al, 2002;Bethke et al, 2007), whereas gibberellins (GA) promoted vacuolation to mobilize the reserve enzymes and compounds to incite aleurone PCD (Bethke et al, 2002;Zhang et al, 2020).…”
Section: Heaep3mentioning
confidence: 99%
“…Primarily, it has been found that VPEs are responsible for the maturation of seed storage proteins such as 2S albumin and 12S globulin [ 20 ]. Now it is known that they participate in other developmental processes [ 21 , 22 , 23 , 24 , 25 , 26 ], senescence [ 27 , 28 , 29 ], and environmental stress responses [ 28 , 30 , 31 , 32 ]. During development, senescence, and plant responses to environmental stimuli, both autophagy [ 11 ] and PCD can be initiated [ 33 ].…”
Section: Functions Of Vpesmentioning
confidence: 99%
“…Upregulation of VPEs occurs in various types of PCD. VPE involvement has been widely demonstrated during developmental PCD (dPCD), including seed coat formation in angiosperms [ 21 ], xylogenesis [ 23 ], development of the root velamen radicum in the epiphytic orchid Cymbidium tracyanum [ 25 ], development of pollen and tapetal cell degradation in Arabidopsis thaliana [ 24 , 26 ], leaf morphogenesis of the lace plant ( Aponogeton madagascariensis ) [ 34 ], and degradation of aleurone layers in rice ( Oryza sativa ) [ 22 , 30 ]. One of the best-known types of PCD regulated by VPEs is the hypersensitive response (HR), which was first observed in VPE-silenced Nicotiana benthamiana infected with tobacco mosaic virus (TMV) [ 35 ].…”
Section: Functions Of Vpesmentioning
confidence: 99%
See 1 more Smart Citation